2009
DOI: 10.1166/jnn.2009.1468
|View full text |Cite
|
Sign up to set email alerts
|

Photoconductive Properties of Selenium Nanowire Photodetectors

Abstract: Selenium nanowires with a diameter of about 70 nm and a growth direction along [001] were fabricated via a facile solution method. Photoconductive properties of Se wires were systematically characterized via photodetectors made of single Se nanowire. The photodetectors exhibited a high light on-off current ratio (Ilight/ Idark) of 450, and a fast light response speed of millisecond rise/fall time with excellent stability and reproducibility. It was also observed that the response time strongly depend on the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…Meanwhile, the clear lattice fringes with d-spacing of $0.4 nm and 0.5 nm correspond to the (100) and (001) lattice planes of hexagonal phase Se, revealing that the nanowire was single crystalline. [27][28][29] The inset describes a fast Fourier transform (FFT) of the image of Fig. 1(h) which is equivalent to an electron diffraction pattern.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the clear lattice fringes with d-spacing of $0.4 nm and 0.5 nm correspond to the (100) and (001) lattice planes of hexagonal phase Se, revealing that the nanowire was single crystalline. [27][28][29] The inset describes a fast Fourier transform (FFT) of the image of Fig. 1(h) which is equivalent to an electron diffraction pattern.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the relatively narrow E g of Se nanomaterials, they are capable of displaying strong broadband optical response behaviors. [2,33,34,159] Gates et al used the UV-vis absorption spectra to in-situ characterize the formation of Se nanowires, as shown in Figure 10a. Aliquots of the product were removed from the mixture at a predetermined time and allowed to naturally cool to room temperature.…”
Section: Optical Propertymentioning
confidence: 99%
“…As a narrow bandgap semiconductor, Se has a helical chain with weak van der Waals interaction which is considered to have potential applications in high-performance electronic/ optoelectronic devices. [33,59,159,[180][181][182] Ye et al [59] demonstrated that 2D Se nanosheets prepared by vacuum vapor deposition, exhibited excellent p-type transport behaviors with an onstate current density ≈20 mA mm −1 at V ds = 3 V with a high on/off ratio of ≈10 6 . Besides, both the photocurrent (I ph ) and responsivity (R λ ) are linearly proportional to the laser power, indicating that I ph is mainly determined by the photoexcited carriers (Figure 13a,b).…”
Section: Electronics/optoelectronicsmentioning
confidence: 99%
“…Zhai et al [174] pursued a similar thermal evaporation method but with Au nanoparticle catalyst. Others include InP NW PDs [136], NWs of CdTe [175], ultraviolet PDs based on single GaN nanorod p-n junctions [176], InAs/InAsP NWs [177], aligned assemblies of core-shell CdSe/CdS nanorods [178], Ge NW with CdS nanoparticle heterojunction [179], single InP NW devices with back-to-back Schottky barriers [180], Se NWs [181], Ge NW PDs [182], [183], InSb-NW-array PDs [184], CdZnS NW networks [185], metal-semiconductor-metal PDs made from an individual CdS NW [186], Ge NW Schottky PDs [79], [187], Bi 2 S 3 NWs [188], 3-D-to-3-D-transferred Si photoconductor [135], and InP NWs [189].…”
Section: A Review Of Various Nw Pds 1) Nw Pds Via Direct Growthmentioning
confidence: 99%